Diagnostic Performance of 99 mTc-Sestamibi SPECT/CT and 18F-Choline PET/CT in Locating Hyperfunctioning Parathyroid Glands in Patients with Primary Hyperparathyroidism - Mandic, Ante; Kraljevic, Ivana; Skoric Polovina, Tanja; Zibar Tomsic, Karin; Dusek, Tina; Balasko, Annemarie; Solak, Mirsala; Kastelan, Darko (Nuklearmedizin - NuclearMedicine, 2025)
This study aimed to assess the diagnostic performance of 99mTc-sestamibi SPECT/CT and 18F-choline PET/CT in detecting hyperfunctioning parathyroid glands in patients undergoing surgery for primary hyperparathyroidism (PHPT).A retrospective analysis was conducted on patients who underwent PHPT-related surgery between April 2019 and May 2022. The study focused on patients undergoing either 99mTc-sestamibi SPECT/CT (81 patients) or 18F-choline PET/CT (33 patients) scans before surgery to pinpoint hyperfunctioning parathyroid gland(s). In the majority of patients, 18F-choline PET/CT was performed after negative or inconclusive findings on 99mTc-sestamibi SPECT/CT. Pathohistological reports were utilized as the reference standard for evaluating the accuracy of the imaging findings.The study encompassed 83 patients (70 females, 84.3 %) with an average age of 57.2 years (24–80 years). The pathohistological analysis identified a total of 98 glands. In a per-lesion analysis, the detection rate of 99mTc-sestamibi SPECT/CT was 57 % (95 % CI 45.3–68.1), while the detection rate of 18F-choline PET/CT was 90.3 % (95 % CI 74.3–98.0).The results of our study showed the significant usefulness of 18F-choline PET/CT in patients with negative or inconclusive results of 99mTc-sestamibi SPECT/CT in accurately locating hyperfunctioning parathyroid glands in PHPT patients.
Keywords: primary hyperparathyroidism; 18F-fluorocholine; PET imaging; 99mTc-sestamibi; SPECT